CROSS-CULTURAL COMPETENCE AS ONE OF THE COMPONENTS OF THE COMMUNICATIVE CULTURE OF STUDENTS IN A POLYETHNIC EDUCATIONAL ENVIRONMENT - Kim, N.P.; Kim, L.M.; Kim, Т.V. (PUBLISHINGS of Kostanay State Pedagogical University, 2020)
This article addresses the issue of the relevance of cross-cultural competence in modern Kazakhstan characterized by multi-ethnicity. The article gives the concept of cross-cultural communication, reveals its main characteristic features. Cross-cultural competence is considered as one of the conditions for achieving effective communication. The non-verbal communication is an important element of communication in a cross-cultural field. The main structural elements and, accordingly, the main ways of forming cross-cultural competence are identified, these are the development of such quail-ties as empathy and tolerance, carried out through learning the different cultures; accumulation of communicative experience in a cross-cultural environment, in the field of the cross-cultural contacts
Keywords: interaction of cultures; cross-cultural communications; cross-cultural competence; multi-ethnic environment.